ANALISIS PENGARUH PERTUMBUHAN KOTA KENDARI TERHADAP PENGEMBANGAN KAWASAN HINTERLAND PROPINSI SULAWESI TENGGARA - Endang Abubakar; Hilmi Hilmansyah; La Ibal (Journal Peqguruang: Conference Series, 2023)
The hinterland area is one part of the nodal area concept, where the division is based on the respective functions of each region. This study aims to analyze the effect of the growth of Kendari City on the development of the hinterland area of Southeast Sulawesi Province. Research using qualitative and quantitative methods with descriptive analysis and spatial analysis The results of the study showed that there was an increase in the interaction between Kendari City and other surrounding sub-districts, namely Ranomeeto District, Sampara District, and Soropia District. The model used to measure the interaction is the gravity model, which produces the gravity number for each sub-district. The district that has the largest gravity number with Kendari City is Ranomeeto District, followed by Sampara District, and finally Soropia District. Distance has a negative relationship with the force of gravity. The closer the distance between the two areas, the greater the gravity number generated, which indicates that the interaction between the two areas is getting bigger. In general, the interaction between Kendari City and its hinterland sub-districts during 2018–2022 has increased, although the increase has slowed down. The interaction between Kendari City and three other surrounding sub-districts, namely Ranomeeto Sub-District, Sampara Sub-District, and Soropia Sub-District, can be categorized as a generative type of relationship, namely a relationship that is mutually beneficial or mutually developing between more advanced regions and the regions behind them.